2014
DOI: 10.1210/en.2013-1820
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Dopamine Receptor Type-2 (DRD2) Promoter by 9-Cis Retinoic Acid in a Cellular Model of Cushing's Disease Mediates the Inhibition of Cell Proliferation and ACTH Secretion Without a Complete Corticotroph-to-Melanotroph Transdifferentiation

Abstract: Cushing's disease (CD) is a rare condition in which hypercortisolemia is secondary to excessive ACTH release from a pituitary corticotroph adenoma. CD is associated with significant morbidity and mortality, and a safe therapy that effectively targets the pituitary tumor is still lacking. Retinoic acid (RA) and dopamine agonists (DAs) have recently been considered as monotherapy in CD patients, and satisfactory results have been reported, albeit in a limited number of patients. Given the permissive role of RA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…As regards ACTH synthesis, we did not observe differences in POMC expression between maleand female-excised adenomas both in unchallenged wells and after CRH/dexamethasone incubation. This finding is in line with the lack of correlation between POMC and ACTH in corticotrope adenomas in vitro [53,54] and, in the present setting, suggests that sexual dimorphism affects POMC peptide processing and secretion rather than POMC transcription.…”
Section: Discussionsupporting
confidence: 91%
“…As regards ACTH synthesis, we did not observe differences in POMC expression between maleand female-excised adenomas both in unchallenged wells and after CRH/dexamethasone incubation. This finding is in line with the lack of correlation between POMC and ACTH in corticotrope adenomas in vitro [53,54] and, in the present setting, suggests that sexual dimorphism affects POMC peptide processing and secretion rather than POMC transcription.…”
Section: Discussionsupporting
confidence: 91%
“…A second fragment for each tissue specimen was immersed in RNAlater (Ambion), kept at 4°C for 24 h and then stored at −20°C until RNA extraction. The remainder of each somatotropinoma was transferred to sterile cold complete culture medium and processed within 36 h as previously described (13). Informed consent was obtained from each patient.…”
Section: Patient Tissues and Primary Cell Culturesmentioning
confidence: 99%
“…Interestingly, these authors reported mRNA and protein expression of retinoic-acid-synthesizing enzyme aldehyde dehydrogenase 1A1 (ALDH1A1 or RALDH1), only in lactotropic cells from males but not from females, and in folliculo-stellate cells (FS) from both sexes [16]. This enzyme catalyzes the conversion of 9-cis-retinal to 9-cis-retinoic acid, which increases the expression of dopamine receptor type 2 (DR2) in normal and pituitary tumors [63,64]. In line with this, promotion of lactotropic cell secretion and proliferation in adults is associated with reduced expression of retinoic-acid-synthesizing enzyme ALDH1, indicating its involvement in this process.…”
Section: Effects Of Estradiol On Differentiated Lactotropic Cells In mentioning
confidence: 99%